Civil War leadership and Mexican War experience - Dougherty, Kevin (University Press of Mississippi, 2007)
A great many commanders in the American Civil War (1861-1865) served in the Mexican War (1846-1848). Civil War Leadership and Mexican War Experience explores the influence of the earlier war on those men who would become leaders of Federal and Confederate forces. Military historian Kevin Dougherty sets the context with a discussion of professional soldiering before both wars. He then depicts the unique experiences of twenty-six men in Mexico, thirteen who would later serve the Confederacy and thirteen who would remain with the Union.